Prevalence of Covid 19 in Students Attended Al-Dora Family Medical Center for Covid 19 Test - Rawa Jaafar Kadhim Al-Ameri (International Journal of Coronaviruses, 2022)
Introduction: Covid 19 pandemic affected all aspect of life, particularly schools attending. Students replaced their presentational lessons by on line distance learn. Ministry of health decisions varied between complete electronic study and attendance several days per week depending on the number of cases of the whole population. In Iraq, total cases till 15 of September, 2021, reached 1.963,264 and total death 21,631. Highest percent of confirmed cases in age group (30-39) years; 24.7%, while in children aged (0-9) years only 1.6%, and in older age group (10-19) years; 7.5%. Cases of covid19 at lower percent in small children and in school age children and tend to increase with age as it reached to 22.6% in age group (20-29). Objectives: Prevalence of covid 19 in students attending AL-dora medical center lab. Comparisons in number of cases of students before and after the school lock –down. Methods: It is a cross sectional study, included the records of schools health unit and lab records of VTM nasal or pharyngeal swab and rapid test in Al-Dora family health center from 1/10/2020 to 15/7/2021. Results: The study included 1711 students, the mean age group was 15.7 (± 4.9) years. The study showed the prevalence of covid19 in students attained the lab was 23.4%, highest percent was in age group >18 years and the lowest percent was in age group 6-12 years. The percent of vaccinated students in academic year 2020/2021 was 0.3 %( 3/1000). There is no significance difference in age group 6-12 years and age group >18 years before closing schools and colleges and after closing while age group 13-18 years showed a significant increase in positive cases after closing schools as cases increase from 18.1% to 25.9% after closing schools. Positive cases showed no significance difference with sex before and after closing. Discussions: The educational path of students in different age groups had broken down. Fear of parents could be justified but it could be exaggerated. School closures were applied almost around the world trying to decrease the potential spread of disease despite early studies suggested this would have less impact than most other non-pharmacological interventions.
Keywords: Covid 19